EL ORDEN DE LAS PALABRAS EN CARITÓN DE AFRODISIAS - Hernández Lara, Carlos (Myrtia, 1987)
Word order in Chariton of Aphrodisias is SVO, though there is little quantitative difference with SOV, a more archaic word order. Chariton is fairly moderate and balanced in this respect. It has neither such a large percentage of the popular structure (SVO) as the New Testament, nor the excessive number of archaims of the aticists. The work represents, therefore, an intermediate type of language, a literary ’koine’.